Class III malocclusion: a challenging treatment using miniscrews for extra anchorage - Matsumoto Mirian Aiko Nakane; Monteiro Patrícia Maria; Mendes Wendes Dias; Ferreira José Tarcísio Lima; Romano Fábio Lourenço; Stuani Maria Bernadete Sasso (Sciendo, 2021)
This article presents the nonsurgical orthodontic treatment of a skeletal Class III malocclusion of an adult patient.